Strategies to enhance routine physical activity in care home residents: the REACH research programme including a cluster feasibility RCT - Anne Forster; Mary Godfrey; John Green; Nicola McMaster; Jennifer Airlie; Bonnie Cundill; Rebecca Lawton; Rebecca Hawkins; Claire Hulme; Karen Birch; Lesley Brown; Robert Cicero; et al. (NIHR Journals Library, 2021)
Background: Care home residents are mainly inactive, leading to increased dependency and low mood. Although exercise classes may increase activity, a more sustainable model is to engage staff and residents in increasing routine activity. Objectives: The objectives were to develop and preliminarily test strategies to enhance the routine physical activity of care home residents to improve their physical, psychological and social well-being through five overlapping workstreams. Design: This trial had a mixed-methods research design to develop and test the feasibility of undertaking an evaluative study consisting of gaining an understanding of the opportunities for and barriers to enhancing physical activity in care homes (workstream 1); testing physical activity assessment instruments (workstream 2); developing an intervention through a process of intervention mapping (workstream 3); refining the provisional intervention in the care home setting and clarifying outcome measurement (workstream 4); and undertaking a cluster randomised feasibility trial of the intervention [introduced via three facilitated workshops at baseline (with physiotherapist input), 2 weeks (with artist input) and 2 months], with embedded process and health economic evaluations (workstream 5). Setting: The trial was set in 12 residential care homes differing in size, location, ownership and provision in Yorkshire, UK. Participants: The participants were elderly residents, carers, managers and staff of care homes. Intervention: The intervention was MoveMore, designed for the whole home, to encourage and support the movement of residents in their daily routines. Main outcome measures: The main outcome measures related to the feasibility and acceptability of implementing a full-scale trial in terms of recruitment and retention of care homes and residents, intervention delivery, completion and reporting of baseline data and outcomes (including hours of accelerometer wear, hours of sedentary behaviour and hours and type of physical activity), and safety and cost data (workstream 5). Results: Workstream 1 - through a detailed understanding of life in a care home, a needs assessment was produced, and barriers to and facilitators of activity were identified. Key factors included ethos of care; organisation, management and delivery of care; use of space; and the residents' daily routines. Workstream 2 - 22 (73.3%) out of 30 residents who wore a hip accelerometer had valid data (≥ 8 hours on ≥ 4 days of the week). Workstream 3 - practical mechanisms for increasing physical activity were developed, informed by an advisory group of stakeholders and outputs from workstreams 1 and 2, framed by the process of intervention mapping. Workstream 4 - action groups were convened in four care homes to refine the intervention, leading to further development of implementation strategies. The intervention, MoveMore, is a whole-home intervention involving engagement with a stakeholder group to implement a cyclical process of change to encourage and support the movement of residents in their daily routines. Workstream 5 - 12 care homes and 153 residents were recruited to the cluster randomised feasibility trial. Recruitment in the care homes varied (40-89%). Five care homes were randomised to the intervention and seven were randomised to usual care. Predetermined progression criteria were recruitment of care homes and residents (green); intervention delivery (amber); and data collection and follow-up - 52% of residents provided usable accelerometer data at 9 months (red), > 75% of residents had reported outcomes at 9 months (green, but self-reported resident outcomes were red), 26% loss of residents to follow-up at 9 months [just missing green criterion (no greater than 25%)] and safety concerns (green). Limitations: Observations of residents' movements were not conducted in private spaces. Working with care home residents to identify appropriate outcome measures was challenging. Take-up of the intervention was suboptimal in some sites. It was not possible to make a reliably informed decision on the most appropriate physical activity end point(s) for future use in a definitive trial. Conclusions: A whole-home intervention was developed that was owned and delivered by staff and was informed by residents and staff. The feasibility of conducting a cluster randomised controlled trial was successfully tested: the target numbers of care homes and residents were recruited, demonstrating that it is possible to recruit care home residents to a cluster randomised trial, although this process was time-consuming and resource heavy. A large data set was collected, which provided a comprehensive picture of the environment, residents and staff in care homes. Extensive quantitative and qualitative work comprehensively explored a neglected area of health and social care research. Completion of ethnographic work in a range of settings enabled the production of an in-depth picture of life in care homes that will be helpful for other researchers considering organisational change in this setting. Future work: The content and delivery of the intervention requires optimisation and the outcome measurement requires further refinement prior to undertaking a full trial evaluation. Consideration could be given to a recommended, simplified, core outcome set, which would facilitate data collection in this population. Trial registration: Current Controlled Trials ISRCTN16076575. Funding: This project was funded by the National Institute for Health Research (NIHR) Programme Grant for Applied Research programme and will be published in full in Programme Grant for Applied Research; Vol. 9, No. 9. See the NIHR Journals Library website for further project information.